Perlindungan Konsumen dalam Pemanfaatan Big Data oleh Pelaku Bisnis di Indonesia: Tinjauan Terhadap Regulasi dan Implementasi Praktik Bisnis - Rizal, Muhammad; Setyoningsih, Erika Vivin (Jurnal Penegakan Hukum dan Keadilan, 2023)
The state must protect consumer rights for consumers to get legal assurance in business. The rapid development of business transactions using electronic media has become a trend in various circles. Users are required to input data in the identity verification form when conducting business transactions online in various marketplaces. Due to this regulation, electronic or e-commerce service providers are required to safeguard personal user data. Various electronic or e-commerce service providers store data in Big Data, including the user's data. The problem in this research was how to protect consumers using Big Data by business actors in Indonesia. This type of research was normative juridical research which examined several related laws and regulations. The results showed that if someone's data was transferred without prior permission, the owner might submit a lawsuit to compensate the court. This was stated in Article 26, paragraph (2) of Law Number 19 of 2016 concerning Information and Electronic Transactions. However, the obstacle was the difficulty of proving in the civil court process in Indonesia, such as technical complexity and perpetrators of crimes often have better skills than victims or investigators. Consumers will legally dispute the alleged leakage of personal data as people with personal data. Therefore, the concept of the right to be forgotten or the right to delete privacy appears.